KONSTRUKSI REALITAS DAN POLITISASI PEREMPUAN DI MEDIA SUARA NTB - Nazar Naamy Nazar (Politea : Jurnal Politik Islam, 2022)
This paper aims to find out how the construction of the reality of women in the mass media is formed in the reporting and trafficking of people with female victims in the Mass Media. This study focused on the text of the news of rape and trafficking in women in May 2016 in the NTB Suara daily. This paper is a qualitative study using the Teun Van Dijk model discourse analysis method. With this method, the committee will see how women's discourse is constructed, politicization and shaped by mass media through text analysis, social cognition and social contexts. The conclusion is that Suara NTB daily constructs women as victims, not as objects of exploitation, because women are placed as the subject of the narrator and given space to tell themselves or the events experienced.